Portugal : Financial Sector Assessment Program; Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2007)
This Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision for Portugal discusses the country's market structure. Portugal's regulatory framework is modern and sound, and highly compliant with international standards. Organic Law (OL) of Banco de Portugal (BdP) provides a clear framework, objectives, and responsibilities for carrying out the supervision of credit institutions, financial companies, and other entities legally subject to the BdP's regulation. The regulatory framework allows the authorities to undertake globally consolidated supervision over internationally active banking groups.